2016
DOI: 10.1021/acs.orglett.6b00863
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of 5-Heteroaryl-Substituted Prolines Useful for Controlling Peptide-Bond Geometry

Abstract: A versatile diastereoselective Friedel-Crafts alkylation reaction of heteroaryl systems with a cyclic enecarbamate for the preparation of 5-heteroaryl-substituted proline analogues in good yields has been developed. These heterocyclic tethered cyclic amino acid building blocks constitute important structural motifs in many biologically active molecules. The impact of the substitution on proline cis/trans isomerization was explored by carrying out solution conformational studies by NMR on 5-furanyl-substituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Initially 2b is formed by the reaction of 1 with indole that rearrange instantly to 3-alkylidene-3H-indole intermediate 2c. [50] It is noteworthy that in all the cases we only get symmetrical BHMs containing amino acids. The structure of compound 3 is confirmed by extensive NMR studies.…”
Section: Resultsmentioning
confidence: 97%
“…Initially 2b is formed by the reaction of 1 with indole that rearrange instantly to 3-alkylidene-3H-indole intermediate 2c. [50] It is noteworthy that in all the cases we only get symmetrical BHMs containing amino acids. The structure of compound 3 is confirmed by extensive NMR studies.…”
Section: Resultsmentioning
confidence: 97%
“…[17] We then investigated platinum and silver catalysts (entries 5-7) and were delighted to find that 58 %y ield of 2a was achieved in the presence of AgOTf (entry 7). Interestingly,Brønsted acids promoted selective formation of 2aa (entries [12][13]. [19] Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…PG = protecting group. In addition, amides containing different substituents on the indole ring also underwent smooth cascade cyclization,p roducing the corresponding 2f-n in good to excellent yields (entries [6][7][8][9][10][11][12][13][14], Finally,i tw as found that the reaction also occurred well with (S)-(+ +)-tert-butylsulfinamide-derived 1e' ',a nd thus the other enatiomer, 2e' ', was specifically produced (entry 15). Further screening of solvents such as toluene and chlorobenzene led to as lightly decreased yield (entries [14][15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Inspired by these results,w ee nvisioned the synthesis of indole-based tropanes might be achieved by such an anti-Markovnikov hydroamination-initiated cascade cyclization of indolyl homopropargyl amides (Scheme 1e). [13] However,a chieving this cascade reaction is highly challenging:1 )how do we prevent the competing exo cyclization of the terminal alkyne partner by the highly nucleophilic indole moiety by at ypical Markovnikov addition; [5] and 2) how do we achieve the desired cascade cyclization but not stop at the dihydropyrrole intermediate. [14] Herein, we describe the realization of unprecedented copper-catalyzed cascade cyclization of indolyl homopropargyl amides, [15] allowing the practical and atom-economical synthesis of ad iverse array of valuable bridged aza-[n.2.1] skeletons (n = 3-6) with excellent diastereoselectivity and enantioselectivity by achirality-transfer strategy.F urthermore,amechanistic rationale for this serial cascade cyclization is strongly supported by av ariety of control experiments,a nd importantly,i ts mechanism is distinctively different from the related gold catalysis.…”
Section: Introductionmentioning
confidence: 99%